COPING STRATEGIES FOR ADAPTATION TO A FOREIGN CULTURAL ENVIRONMENT (American Journal of Research in Humanities and Social Sciences, 2024)
The article is devoted to the topical issue of adaptation to a foreign cultural environment and the connection between the success of adaptation and the use of various coping strategies: it summarizes theoretical provisions on the adaptation process, the concepts of "stress" and "coping strategies". It describes various approaches to adaptation as a stressful situation and the classification of coping strategies. The processes of coping and adaptation necessary for a comprehensive analysis of the situation of a person's stay in a new culture are considered. The connection between the choice of the type of coping strategy (cognitive, emotional or behavioral) and the use of certain acculturation strategies is shown. It is emphasized that successful adaptation requires social and psychological work with the processes and phenomena that determine the use of effective coping strategies.